Risk-benefit assessment of cereal-based foods consumed by portuguese children aged 6 to 36 months: a case study under the riskbenefit4eu project - Assunção, R (2021)
Cereal-based foods, including breakfast (BC) and infant cereals (IC), are among the first solid foods introduced to infants. BC and IC are sources of macro and micronutrients that have bene-ficial effects on health, but can also be sources of harmful chemical and microbiological contaminants and nutrients that may lead to adverse health effects at high consumption levels. This study was performed under the RiskBenefit4EU project with the aim of assessing the health impact associated with consumption of BC and IC by Portuguese children under 35 months. Adverse effects associated with the presence of aflatoxins, Bacillus cereus, sodium and free sugars were assessed against the benefits of fiber intake. We applied a riskbenefit assessment approach, and quantified the health impact of changes in consumption of BC and IC from current to various alternative consumption scenarios. Health impact was assessed in terms of disability-adjusted life years. Results showed that moving from the current consumption scenario to considered alternative scenarios results in a gain of healthy life years. Portuguese children can benefit from exchanging intake of IC to BC, if the BC consumed has an adequate nutritional profile in terms of fiber, sodium and free sugars, with levels of aflatoxins reduced as much as possible. (c) 2021 by the authors. Licensee MDPI, Basel, Switzerland.